Comparison between the Acute Effects of Intermittent Hypoxia and Aerobic Exercise on the Nitric Oxide Value, Blood Pressure and the Respiratory Function in Apnea - Latifnezhad 1*, Ronak; Younesian 1, Ali -; Tadibi 2, Vahid (Shahroud Journal of Medical Sciences, 2019)
Background: Apnea is a common disorder in the community. The aim of the study was to compare the acute effects of activity and periodic hypoxia on the nitric oxide, blood pressure, and the pulmonary function in apnea. Methods: The study was as a clinical, pretest, and posttest intervention. A total of 11 males enrolled in the study and completed at least four options of the STOP-Bang inventory. They performed aerobic exercise on a treadmill with intensity of 70 0/0 heart rate reserve, during 40 minutes in intermittent hypoxia. The subjects inhaled intermittently 5 minutes normoxic and hypoxic (11%) air at sitting position for 1 hour. Nitric oxide, blood pressure, and lung function were measured before and after interventions. SPSS22 was used to analyze the collected data. Kolmogorov-Smirnov, ANOVA, and Pearson correlation tests were used. The significance level was set at 0.05. Results: Significantly elevated nitric oxide and reduced systolic blood pressure were observed at 40, 50 and 60 minutes in the intermittent aerobic exercise (Pvalue ≤ 0.05). We found a significant relationship between reduction in systolic blood pressure at 50 minutes and PEF in post 30 and 60 minutes. The results revealed heightened serum nitric oxide after aerobic exercise sessions and diminished systolic blood pressure. However, there was no difference in the lung function factors before and after the interventions. Conclusions: Aerobic exercise increases the nitric oxide better than hypoxia does and reduces blood pressure. Thus, it can be used in patients with obstructive sleep apnea. Keywords: Nitric oxide, Acute training, Lung function, Apnea.